Physiological and Biochemical Effects of Intrinsically High and Low Exercise Capacities Through Multiomics Approaches - Tung, Yu-Tang; Hsu, Yi-Ju; Liao, Chen-Chung; Ho, Shang-Tse; Huang, Chi-Chang; Huang, Wen-Ching (Frontiers in Physiology, 2019)
Regular exercise prevents lipid abnormalities and diabetes mellitus, hypertension, and obesity development, and it benefits sedentary individuals. However, individuals exhibit highly variable responses to exercise, which may be mainly mediated by genetic variations. Animal models are typically used to investigate the relationship of intrinsic exercise capacity with physiological, pathological, psychological, behavioral, and metabolic disorders. In this study, we investigated differential physiological adaptations caused by intrinsic exercise capacity and explored the regulatory molecules or mechanisms through multiomics approaches. Outbred ICR mice (n = 100) performed an exhaustive swimming test and were ranked based on the exhaustive swimming time to distinguish intrinsically high- and low-capacity groups. Exercise performance, exercise fatigue indexes, glucose tolerance, and body compositions were assessed during the experimental processes. Furthermore, the gut microbiota, transcriptome, and proteome of mice with intrinsically high exercise capacity (HEC) and low exercise capacity (LEC) were further analyzed to reveal the most influential factors associated with differential exercise capacities. HEC mice outperformed LEC mice in physical activities (exhaustive swimming and forelimb grip strength tests) and exhibited higher glucose tolerance than LEC mice. Exercise-induced peripheral fatigue and the level of injury biomarkers (lactate, ammonia, creatine kinase, and aspartate aminotransferase) were also significantly lower in HEC mice than in LEC mice. Furthermore, the gut of the HEC group contained significantly more Butyricicoccus probiotics than did the LEC group. In addition, the transcriptome data of the soleus muscle revealed that the expression of micro-RNAs strongly associated with exercise performance-related physiological and metabolic functions (i.e., miR-383, miR-107, miR-30b, miR-669m, miR-191, miR-218, and miR-224) was higher in HEC mice than in LEC mice. The functional proteome data indicated that the levels of key proteins related to muscle function and carbohydrate metabolism were also significantly higher in HEC mice than in LEC mice. Our study demonstrated that the gut microbiome, transcriptome, and proteome could elucidate the regulatory effects contributed by different mechanisms to physiological adaptation and exercise capacity.